A Systematic Review and Meta-Analysis of Machine Perfusion vs. Static Cold Storage of Liver Allografts on Liver Transplantation Outcomes: The Future Direction of Graft Preservation - Jia, Junjun; Nie, Yu; Li, Jianhui; Xie, Haiyang; Zhou, Lin; Yu, Jun; Zheng, Shu-Sen (Frontiers in Medicine, 2020)
Background: Machine perfusion (MP) and static cold storage (CS) are two prevalent methods for liver allograft preservation. However, the preferred method remains controversial. Aim：To conducted a meta-analysis on the impact of MP preservation on liver transplant outcome. Methods: The Pubmed, EMBASE and Cochrane Library databases were systematically searched to identify relevant trials comparing the efficacy of MP versus CS. Odds ratios (OR) and fixed effects models were calculated to compare the pooled data. Results: 10 prospective cohort studies and 2 randomized controlled trials were included(MP livers versus CS livers = 315 : 489). Machine perfusion demonstrated superior outcomes in post transplantation AST levels compared to CS (P<0.05). The overall incidence of early allograft dysfunction (EAD) was significantly reduced with MP preservation than CS (OR=0.46; 95% CI, 0.31-0.67; P<0.0001). The incidence of total biliary complications (OR=0.53; 95% CI, 0.34-0.83; P=0.006) and ischemic cholangiopathy (OR=0.39; 95% CI, 0.18-0.85; P=0.02) were significantly lower in recipients with MP preservation compared with CS preservation. Hypothermic machine perfusion (HMP) but not normothermic machine perfusion (NMP) was found to significantly protect grafts from total biliary complications and ischemic cholangiopathy (P<0.05). However, no significant differences could be detected utilizing either HMP or NMP in primary non-function, hepatic artery thrombosis, post-reperfusion syndrome, one year patient survival or one year graft survival (P>0.05). Conclusions: MP is superior to CS on improving short-term outcomes for human LT, with a less clear effect in the longer-term. HMP but not NMP conducted significantly protective effects on EAD and biliary complications. Further RCTs are warranted to confirm MP’s superiority and applications.